Teaching the early modern period - Clarke, Danielle (Basingstoke ; New York : Palgrave Macmillan, 2011)
Essays by modernists from wide geographical and disciplinary backgrounds
Includes bibliographical references and index
EDU
Keywords: Literature -- Early modern, 1500-1700 -- Study and teaching (Higher); History, Modern -- 16th century -- Study and teaching (Higher); History, Modern -- 17th century -- Study and teaching (Higher); English literature -- Early modern, 1500-1700 -- Study and teaching (Higher); French literature -- 16th century -- Study and teaching (Higher); French literature -- 17th century -- Study and teaching (Higher)